Development of laser-based system to determine fault surface morphology at the micron scale. (August 2021) - Hao, Haijian; Wei, Zhanyu; He, Honglin; Liu, Liqiang
Graphical abstract: Highlights: A morphology measurement system was based on the laser triangulation principle. A new method with a pre-scanning step and a specific storage format was proposed. A system features a combination of a laser sensor and a 2-dimension traversing frame. The measurement results are high accuracy and high resolution. Abstract: Fault surface morphology plays an important role in the earthquake rupture process. However, determining the frictional surface morphology at the micron scale is challenging owing to the lack of reliable measurement instruments. To overcome the existing instruments' limitations, we developed a novel system. The system effectively measures the steep slope generated in the adjacent fault striations and fault steps. The single measurement area is large, with a value of 30 cm × 30 cm. Furthermore, the developed instrument has a horizontal (X and Y orientations) and vertical (Z orientation) positioning uncertainty of 3.5 μm and 4.5 μm (Z orientation), and a horizontal and vertical resolution of 0.5 μm and 0.076 μm, respectively, which are better than those of existing instruments. The proposed device can be used to practically evaluate the wear surface's shape to obtain high-accurate point cloud data, satisfying the engineering requirements for morphological analyses.